2006
DOI: 10.3349/ymj.2006.47.6.817
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Analysis in Biliary Tract Cancer

Abstract: The etiology of biliary tract cancer is obscure, but there are evidences that bile acid plays a role in carcinogenesis. To find the association between biliary tract cancer and bile acid, this study compared the bile acid concentration and composition among patients with biliary cancer, biliary tract stones, and no biliary disease. Bile was compared among patients with biliary tract cancer (n = 26), biliary tract stones (n = 29), and disease free controls (n = 9). Samples were obtained by percutaneous transhep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…The serum total bilirubin showed a marked difference for bile duct cancer (7.6±3.2 mg/dl) when compared to gall stone formation (2.5±0.8 mg/dl) as there was severe obstruction in cancer cases (p: 0.0001*). The study done by park also showed similar results (Park et al, 2006). In both cancer and stone cases, mildly raised AST and ALT suggested the very less injury to hepatocytes.…”
Section: Discussionsupporting
confidence: 70%
“…The serum total bilirubin showed a marked difference for bile duct cancer (7.6±3.2 mg/dl) when compared to gall stone formation (2.5±0.8 mg/dl) as there was severe obstruction in cancer cases (p: 0.0001*). The study done by park also showed similar results (Park et al, 2006). In both cancer and stone cases, mildly raised AST and ALT suggested the very less injury to hepatocytes.…”
Section: Discussionsupporting
confidence: 70%
“…The increased levels of deoxycholic acid in the bile of these patients might be related to their disease, because an increase in deoxycholic acid has been described to be associated with an enhanced induction of gallbladder polyps in hamsters (39). However, in Asian subjects, a higher level of deoxycholic acid in healthy liver transplant donors has also been reported, suggesting that differences in biliary bile acid composition may exist between control groups of different ethnicity (40). In the Chilean study (38), the majority of the patients enrolled in the reference group underwent surgical procedures because of gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…GDCA was reported to play an important role in the detoxification of lipophilic compounds [49]. Decreased serum bile acids have been related to the accumulation of toxic and even carcinogenic bile acid in liver that may be caused by the alteration in the bile acid transport pathway [50]. GCDCA has been reported as an inducer of apoptosis in human hepatocyte [51].…”
Section: Liver Cirrhosis and Chronic Liver Diseasesmentioning
confidence: 99%